THE EFFECT OF DIET AND PHYSICAL ACTIVITY ON TOTAL CHOLESTEROL LEVELS - Nurdin, Fatah; Yuliasih; Diyananda, Dzulfiqar; Ihsani, Sri Indah; Oktafiranda, Nadya Dwi; Yuliana, Ela (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study was to determine the effect of diet and physical activity on total cholesterol levels. The method used is a descriptive method with survey techniques. The population of study program coordinators within UNJ and the sampling technique with random sampling is that all populations have the same opportunity to be sampled. The result of this study is that the frequency (X1) to cholesterol (Y) has a correlation of -0.434 meaning that there is a negative correlation between the frequency of exercise and cholesterol and significant because the significant number is 0.027 below 0.05. This means that the more often you exercise, the lower your cholesterol. While diet (X2) to cholesterol (Y) has a correlation of -0.418 there is a negative correlation between diet and the amount of cholesterol and significant because the significant number is 0.034 below 0.05. This means that by managing a good diet, the cholesterol is getting lower. So the conclusion is that the more often you exercise, the lower the cholesterol, and the better you regulate your diet, the lower the cholesterol.